Degradation of black tea theaflavin through C-ring cleavage by gut microbiota - Shuwei Zhang; Christina Ohland; Christian Jobin; Shengmin Sang (Food Science and Human Wellness)
ABSTRACT: Increasing evidence has shown that gut microbiota plays important roles in metabolizing large molecular polyphenols to bioavailable and bioactive microbial metabolites. Theaflavin (TF) is one of the major color compounds in black tea and has demonstrated anti-inflammation, antioxidant, and anticancer effects properties. However, little is known about the metabolism of TF by gut microbiota in vivo. In this study, following the administration of TF to mice, the C-ring cleavage metabolites, dihydro- and tetrahydro-theaflavin (DH-TF and TH-TF) were detected in mouse feces by LC-MS and validated by authentic standards from in situ chemical reaction. The observation of the C-ring cleavage metabolites in TF-treated conventionalized mice but not in germ-free (GF) mice confirmed the role of gut microbiota in cleaving the C-rings of TF. The detection of DH-TF from the anaerobic incubation of TF with catechin-converting gut bacteria, Eggerthella lenta (Eggerth), suggested that the microbes with the capacity to cleave the C-ring of catechins were able to metabolize TF following the same mechanism. Additionally, three small phenolic metabolites were detected in mouse feces, and one of them was primarily detected in SPF mice not GF mice, which revealed that TF, subsequent to the cleaved C-ring, can be further metabolized into smaller phenolic metabolites by gut microbiota. Dose-dependent production of these metabolites were observed from the administration of 100 mg/kg to 400 mg/kg body weight of TF. In conclusion, gut microbiota can metabolize TF to the open-ring metabolites and the phenolic metabolites through the C-ring cleavage in mice.